Pengaruh Media Pembelajaran Interaktif Berbasis Articulate Storyline 3 terhadap Hasil Belajar Matematika Siswa Kelas IV - Asri, Ainun; Sukriadi, Sukriadi; Arafah, Andi Asrafiani; Muhlis, Muhlis; Septika, Hety Diana; Haerani, Rosita Putri Rahmi (AS-SABIQUN, 2025)
This research is motivated by the low mathematics learning outcomes of grade IV students of SDN 007 Sungai Kunjang. This is due to several factors, one of which is the lack of use of learning media used by teachers. The purpose of this study is to determine the effect of the use of interactive learning media based on Articulate Storyline 3 on the mathematics learning outcomes of students of number material up to 10,000 in grade IV of SDN 007 Sungai Kunjang. The research method used is quantitative research with a quasi-experimental design, using the entire existing population as a research sample totaling 52 students consisting of 26 students from class IV B as the experimental class and 26 students from class IV A as the control class selected through saturated sampling techniques. The post-test results obtained from the study showed that the average score of mathematics learning outcomes in the experimental class was 77.32 while in the control class the average was 67.09. The results of data analysis with the Independent t-test obtained were the significance value (2-tailed) = 0.002. Based on the decision-making basis of the Independent t-test, if the significance value (2-tailed) < 0.05, then Hα is accepted and H0 is rejected. Thus, because the significance value (2-tailed) obtained is less than 0.05, it can be concluded that there is an effect of the use of interactive learning media based on Articulate Storyline 3 on the mathematics learning outcomes of students with number material up to 10,000 in grade IV of SDN 007 Sungai Kunjang. This research contributes to the development of learning innovations in mathematics learning and the improvement of student learning outcomes.